KONSEP GRAPHIC INDUSTRIAL PADA DESAIN INTERIOR PERUSAHAAN SOUVENIR & GIFT BERBASIS KARIKATUR DI SURABAYA - Ariani Wijaya; Astrid Kusumowidagdo; Stephanus Evert Indrawan (KREASI, 2016)
Nowadays community lifestyle has rapidly growing in society, these are directly affecting the business development in Indonesia especially souvenir and gift business that specialized in face caricature, Illustration and silhouette. Communities are often having a difficulty to find a souvenir & gift that are unique and memorable yet multifunctional. These souvenir and gift are commonly used in variety events such as graduation, farewells, anniversaries and so on. Although consumers required to have a direct inspection of product quality, shape, and function. However these caricature souvenirs and gifts are hardly can be found in many retail stores in Surabaya. Therefore, NGIDE (art and craft venture space) is an innovative solution that created to meet consumer’s demand. In the initial phase, NGIDE (art and craft venture space) will be based on online shop, which sells souvenir and gift. Afterward, in the third phase, NGIDE (art and craft venture space) will be developed as building facility, which contains retail area, mini eatery, office, studio and meeting room. Consumers are able to freely choose product variant and consult their needs in the retail area. Furthermore, to give an extra added value, some of the souvenir and gift working progress can be awaited thus mini eatery is provided. Customers can relax and enjoy their meal in this area. Other facilities such as studio, office and meeting room are designated for employees as the production area. Besides, NGIDE (art and craft venture space)’s interior are designed with industrial style that combines the implementation of graphic and exposed material to outshine company identity as souvenir and gift company which specialized in caricature, illustration, and silhouette; and the focus of NGIDE (art and craft venture space)’s brand personality itself will be creative, fun and fresh. The purpose of designing interior architecture of NGIDE (art and craft venture space) is not only improving business development but also creating brand new art and craft space in Surabaya.